Strategi Peningkatan Distribusi Zakat Profesi UPZ Al Hurriyyah di Sekitar Masyarakat Lingkar Kampus IPB - Fenty Wurni Asih; Dika Nugraha; Arinda Gaby Trisila; Neneng Hasanah (AL-MUZARA'AH, 2024)
The distribution of professional zakat funds from the Al-Hurriyyah IPB Zakat Collection Unit (UPZ) focuses on the educational sector, namely in the form of scholarships for IPB students who meet the criteria. However, this shows that distribution at UPZ Al-Hurriyyah IPB has not been optimal because it only focuses on one area, namely the educational scholarship program for IPB students who need UKT assistance and living costs. There needs to be other programs, such as community economic empowerment programs, so that the distribution of professional zakat in UPZ al-Hurriyyah is more even in distribution. This research aims to determine strategies for increasing the distribution of professional zakat at UPZ Al-Hurriyyah. The method used in the research is qualitative with ANP-SWOT analysis. The data used is primary data from questionnaires distributed to five respondents. The results of the research show that the threat aspect is a priority that influences UPZ Al-Hurriyyah in distributing professional zakat funds. Weaknesses, opportunities and strengths are the next priority in the ANP-SWOT analysis. The strategy recommendations that can be given include strengthening branding through offline and online platforms.